An Analysis of Verb Pattern Errors in Active-Passive/Passive-Active Sentence Transformation in English made by Upper Primary Singaporean & Malaysian Chinese Children with Specific Language Impairment - Noel Kok Hwee Chia, Esther Yap & Angie Gek Tee Ng (Journal of the American Academy of Special Education Professionals, 2010)
Very little research studies have been done in Singapore and Malaysia on children with specific language impairment (SLI). Although, it is still unclear what SLI exactly is, most professionals in this part of the world accept it as a specific learning difficulty (like dyslexia) because one set of skills (spoken language) is less well developed than another (visual-perceptual abilities). One of the biggest challenges that children with SLI face is to understand the verb morphology. Moreover, most teachers of English as a Second language (TESL) in Singapore and Malaysia have found the topic challenging to teach and more so when they have to teach active-passive/passive-active sentence transformation. In this study, 27 upper primary school children of Chinese descent – 12 from the Learning Disabilities Center, Singapore, and 15 from the EY Ucapan Klinik, Malaysia – were identified to manifest SLI and invited to participate in the research. The authors of this paper have chosen to examine the various verb pattern errors in active-passive/passive/active sentence transformation committed by these children and also suggested a pedagogical approach to teach active-passive sentence transformation.